Avaliação das emissões de hidrocarbonetos policíclicos aromáticos e seus derivados a partir de matrizes asfálticas - Cargnin, Rejane Secretti (2022)
Asphalt is a product of petroleum, basically consisting of hydrocarbons, which may contain heteroatoms such as sulfur, oxygen and nitrogen in their structure. In the application of asphalt on a road bed, it is subjected to heating in order to reduce viscosity and facilitate handling. In this process, the volatile organic compounds (VOCs) of the asphalt composition, are emitted in the gaseous phase (asphalt fumes), exposing workers to occupational risk, which is one of the main sources that are aggravating and harmful to workers' health. In this context, the objective of this work is to evaluate the presence of polycyclic aromatic hydrocarbons (PAHs) and their sulfur derivatives (PASHs), oxygenated (OPAHs) and nitrogen (NPAHs) in asphalt fumes. For the study of emissions, asphalt samples from three refineries in Brazil were evaluated, in addition to a sample modified by Styrene-Butadiene-Styrene (SBS) polymer, at temperatures of 130 ºC, 160 ºC and 200 °C. To promote the emission of compounds present in the samples, an Extraction and Collection Device (ECD) was used. For the analysis of the emitted compounds, the technique of High Performance Liquid Chromatography with diode array detection (HPLC-DAD) was used. To quantify the PASHs, a chromatographic method for the separation of 28 PASHs was developed and their analytical characteristics were evaluated. As well as a method for separating 5 OPAHs and 5 NPAHs by HPLC-DAD. The developed methodologies showed good precision and accuracy, and the detection and quantification limits were low, considering the concentration found in the emissions. Using the aforementioned analytical methodologies, the samples were characterized and presented at least 33 of the 54 compounds within the scope of this study. The emission is highly dependent on the heating temperature of the asphalt. An increase in asphalt application temperature leads to a higher concentration of emitted compounds. Furthermore, compounds of higher molecular weight were only detected at higher temperatures of the asphalt mass, while those with lower molecular weights are easily detached from the asphalt mass and released into the environment. As a result, more compounds could be detected from asphalt fumes generated at 200 ºC and 160 °C compared to those generated at 130 °C. The results obtained indicate that even at temperatures below their boiling points the compounds can be emitted. The asphalt source also significantly affects the compounds and the amount emitted. There is a strong predominance of PAHs in emissions followed by PASHs and OPAHs for Petroleum Asphalt Cements CAP 1, CAP 2 and CAP 3, without the presence of NPAHs in these asphalt matrices. The CAP 4 sample behaves a little differently from the others. The emission of PAHs is equally dominant, however, in relation to quantification, for this sample OPAHs predominate in relation to PASHs. Still, there is the contribution of NPAHs in the emissions of this sample.